Analysis of Competency and Commitment to Employee Performance in University (Systematic Literature Review) - Jumawan; Zahara Tussoleha Rony (PT FORMOSA CENDEKIA GLOBAL, 2023)
This scientific article presents the application of competence, commitment, and performance of employees in universities, and also the importance of these three variables in higher education. The research method used is that the technique in reflection is graphic, the analyst gathers the specified information from additional sources and analyzes and refines it if necessary. Research information is collected through additional data. Supporting information is collected through google scholar, Elsevier books, and research. The scored PICO framework (population/problem, intervention, comparison) was used to determine the scope of the study. Research results from the three variables in this article provide a result of scientific articles that have been studied with objects in universities so that these three variables are jointly used in the treasures of science, especially in human resources. The three variables in this article can be a reference for other researchers to use together in a future study with the same research object or different methods, so as to produce research that can contribute to the general public